Immunochemical faecal occult blood testing to screen for colorectal cancer: Can the screening interval be extended? - Haug, U.; Grobbee, E.; Lansdorp-Vogelaar, Iris; Spaander, M.; Kuipers, E. (2016)
Objective: Colorectal cancer (CRC) screening programmes based on faecal immunochemical testing for haemoglobin (FIT) typically use a screening interval of 2 years. We aimed to estimate how alternative FIT strategies that use a lower than usual positivity threshold followed by a longer screening interval compare with conventional strategies. Methods: We analysed longitudinal data of 4523 Dutch individuals (50-74 years at baseline) participating in round I of a one-sample FIT screening programme, of which 3427 individuals also participated in round II after 1-3 years. The cohort was followed until 2 years after round II. In both rounds, a cut-off level of =50 ng haemoglobin (Hb)/mL buffer (corresponding to 10 mg Hb/g faeces) was used, representing the standard scenario. We determined the cumulative positivity rate (PR) and the numbers of subjects diagnosed with advanced adenomas (N_AdvAd) and early stage CRC (N_earlyCRC) in the cohort over two rounds of screening (standard scenario) and compared it with hypothetical single-round screening with use of a lower cut-off and omission of the second round (alternative scenario). Results: In the standard scenario, the cumulative (ie, round I and II combined) PR, N_AdvAd and N_earlyCRC were 13%, 180% and 26%, respectively. In alternative scenarios using a cut-off level of respectively =11 and =22 ng/HbmL buffer (corresponding to 2 and 4 mg Hb/g faeces), the PRs were 18% and 13%, the N_AdvAd were 180 and 162 and the N_earlyCRC ranged between 22-27 and 22-26. Conclusions: The diagnostic yield of FIT screening using a lowered positivity threshold in combination with an extended screening interval (up to 5 years) may be similar to conventional FIT strategies. This justifies and motivates further research steps in this direction.